Highly enantioselective synthesis of sitagliptin - Khopade, V. Kishor; Sen, Anirban; Birajdar, Rajkumar S.; Paulbudhe, Uday P.; Kavale, Dattatry S.; Shinde, Prashant S.; Mhaske, Santosh B.; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2020)
A highly enantioselective synthesis of sitagliptin, a potent DPP-4 inhibitor, is reported. Explicitly identified chiral FerroLANE ligands in the presence of rhodium catalyze the asymmetric hydrogenation of an enamine to yield sitagliptin with excellent enantioselectivity (98% ee). The process was scaled up to 5 g and the final product was isolated as a phosphate salt with >99% ee.
Keywords: asymmetric hydrogenation; catalysis; FerroLANE ligands; Rhodium; sitagliptin

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Insertion copolymerization of functional olefins: Quo Vadis? - Birajdar, Rajkumar S.; Chikkali, Samir H. (European Polymer Journal, 2021)
Functional polyethylene is a specialty polymer with unique set of properties and caters to a niche market. Currently, it is manufactured using high-pressure, high-temperature radical polymerization, or post-reactor (indirect) modification methods. Insertion copolymerization of functional olefins with ethylene provides a low pressure, direct route to prepare functional polyethylenes. However, insertion copolymerization of functional olefins with ethylene poses several impediments and requires special considerations. This review presents the current strategies, examines the progress, and attempts to gauge the commercial potential of direct synthesis of functional polyethylene. The performance of late transition metal catalysts derived from a-diimine, imine-phenolate, phosphine-sulfonate, bis-phosphine-mono-oxide, carbene-phenolate, phosphine-phenolate and their derivatives in the insertion copolymerization of functional olefins with ethylene is evaluated. While catalyst designing is crucial, incorporation of polar olefins that can serve an additional purpose is equally important. Therefore, we have organized the review in the following sections, polar alkenes with- acrylates, acrylic acids, acetates, nitriles, ethers, halides, two functional groups, cross-linking groups, dynamic interactions/self-healing properties, additional function/purpose, renewable functional olefins, and examine the progress. Among these, acrylates have been most intensively investigated and have been successfully incorporated in the polyethylene main-chain. Ethylene, methyl acrylate copolymers prepared by direct copolymerization reveal comparable melting temperature to that of LLDPE (at similar co-monomer content) and unfold the commercial potential of these materials. Recent developments on the insertion copolymerization of renewable functional olefins and di-functional olefins have elicited significant interest. This strategy is being viewed as a means of reducing environmental impact and enabling high functional group density at the same extent of incorporation. The overview thus offers a succinct account of insertion copolymerization of functional olefins, sheds light on the copolymer microstructure/material properties, and initiates a discussion on the commercial potential of functional polyethylene.
Keywords: Catalyst; Functional polyethylene; functional polyolefins; Hydrophilic polyethylene; insertion copolymerization; Polyethylene

Emerging trends in olefin polymerization: a perspective - Birajdar, Rajkumar S.; Bodkhe, Dnyaneshwar; Gupta, Poonam; Shaikh, Maulali H.; Ramekar, Rohan; Chikkali, Samir H. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
The seemingly matured field of olefin polymerization still poses several challenges and holds enormous potential to meet contemporary material requirements. In this feature article, we examine the progress of olefin polymerization in the last two decades. Among the several emerging trends, we identify four most impactful discoveries, namely, (i) disentangled ultra-high molecular weight polyethylene (dUHMWPE), (ii) disubstituted functional olefin copolymerization, (iii) incorporation of bioderived comonomers in polyolefins, and (iv) application of above (ii, iii) functional polyolefins as compatibilizers. The dUHMWPE has attracted significant attention and heterogeneous Ziegler-type catalysts, homogenous metallocene, and post-metallocene catalysts have been reported to produce disentangled ultrahigh molecular weight polyethylene. Insertion copolymerization of difunctional disubstituted olefins has been reported only recently and ortho-phosphinobenzene sulfonate palladium catalyst outperforms the other catalysts. Interestingly, insertion copolymerization of bioderived olefins has witnessed a surge in the number of reports. Sugar and plant oil-derived olefins have been copolymerized with ethylene to obtain relatively hydrophilic polyethylene. The functional polyethylene is finding a new application as compatibilizer or displays better adhesion to surfaces. Thus, the feature article offers a succinct account of emerging trends in polyolefins, identifies the most impactful contributions, and debates the application potential of these new materials.
Keywords: compatibilizer; Functional polyethylene; Insertion (co)polymerization; renewable monomers; uHMWPE

Palladium-catalyzed polar solvent empowered synthesis of hyper-branched ethylene oligomers and their applications - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Pol, Harshawardhan V.; Prabhu, M. Basava; Rokade, Dhammaraj; Nandimath, Sheetal; Chikkali, Samir H. (Polymer Chemistry, 2023)
In this contribution, we report the synthesis of two naphthoxy imine ligands, 2-(((2,6-dibenzhydryl-4-methoxyphenyl)imino)methyl)naphthalen-1-ol (L1) and 2-(((2,6-diisopropylphenyl)imino)methyl)naphthalen-1-ol (L2), with different steric and electronic features. L1 and L2 were treated with [(TMEDA)PdMe2] to obtain the corresponding neutral palladium(ii) complexes Cat.1 and Cat.2 in excellent yields. The identity of Cat.1 and Cat.2 was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. When exposed to 5 bar ethylene pressure, Cat.1 produced hyperbranched ethylene oligomers. The microstructure analysis of ethylene oligomers confirmed the existence of methyl, ethyl, propyl, and sec-butyl branches, with a molecular weight (M-n) of 500-1400 g mol(-1), a PDI of 1.46-2.10, and 67-106 branches per 1000 carbon atoms. The use of a polar solvent, tetrahydrofuran, led to a remarkable 3-fold increase in oligomerization activity without compromising the branching and molecular weight. The resultant hyperbranched ethylene oligomers were selectively monofunctionalized using industrially practiced hydroformylation, ozonolysis, and epoxidation, almost quantitatively. The hydroxy functionalized ethylene oligomer (F4) (5 wt%) was melt-compounded with LLDPE and Nylon-6 to produce a tough yet flexible blend with a higher strain-to-failure as compared to an uncompatibilized blend.

Regulating the polyethylene microstructure by increasing steric crowding in naphthoxy imine-ligated Ni(II) complexes - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Polymer Chemistry, 2024)
Ligands play a prominent role in ethylene polymerization. However, it is a highly challenging task to regulate branching through ligand modifications. Here we report the synthesis of systematically sterically tailored naphthoxy imine-ligated nickel complexes (Ni1, Ni2, and Ni3), their performance in ethylene polymerization, and how the ligand steric controls branching in the resultant PE. Ni1-Ni3 were prepared in one step with an excellent yield (73-93%). The identity of these complexes was unambiguously ascertained using H-1, C-13, 2D NMR spectroscopy, mass analysis, and single-crystal X-ray diffraction. The molecular structure revealed a cis arrangement of alkyl/aryl and donor groups (C-Ni-D), which is necessary for initiating ethylene polymerization. Buried volume contours suggested Ni3 to be sterically the most bulky among the three. When exposed to ethylene, the three nickel complexes Ni1, Ni2, and Ni3 produced polyethylene with excellent activity. As predicted by buried volume calculations, dibenzhydryl-substituted Ni3 outperformed sterically less crowded Ni1 and Ni2. Careful analysis of the resultant PE disclosed that sterically less encumbered Ni1 and Ni2 produce PE with high branching (43-54 branches/1000-C atoms) density. However, the bulkiest Ni3 revealed much lower branching (28 branches/1000-C atoms) and a high TOF of 35 400 mol of PE per mol of Ni per h, along with a high molecular weight of PE (61 000 Da). The steric bulk in Ni3, most likely, reduces chain-walking and thus lowers branching in the resultant PE. As compared to the literature-reported analogous Pd1 catalyst, the Ni3 catalyst discloses high TOF, high molecular weight, and less branched, linear polyethylene.
Keywords: Catalyzed Olefin Polymerization; High-Temperature; Molecular Weight

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Synthesis of imine-phenoxy ligated palladium complexes for norbornene homopolymerization - Birajdar, Rajkumar S.; Gupta, Poonam; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2024)
Metal complexes with tunable ligands play a crucial role in olefin polymerization and impart control over molecular weight, crystallinity, and stereoregularity. We report the single-step synthesis of imine-phenoxy ligands in excellent yields (81-93%). The identity of electronically tuned imine-phenoxy ligands was unambiguously ascertained by using a combination of spectroscopic and analytical methods. These ligands were treated with [Pd(COD)MeCl] in the presence of 2,6-lutidine, resulting in the formation of discrete mononuclear palladium complexes Pd1-Pd4 in excellent yields. 1-2D NMR spectroscopy, mass spectrometry analysis, and single-crystal X-ray diffraction confirmed the identity of the palladium complexes. X-ray analysis revealed a distorted square planar geometry around the palladium center. Proton NMR analysis suggested that the Pd1 catalyst was deshielded, indicating electronically deficient palladium metal compared to the other complexes. Moreover, the Pd1 catalyst showed the highest buried volume percentage (%Vbur = 44.9). When exposed to norbornene, Pd1-Pd4 were found to be active and produced poly(norbornene) (PNB). High-temperature SEC analysis revealed that the electronically deficient and sterically hindered Pd1 catalyst produced the highest molecular weight polymer (PNB 37.4 kDa). Boron and aluminum-based cocatalysts were screened, and MMAO was found to outperform others with high catalytic activity (up to 63.2 x 105 g of PNB (mol Pd)-1 h-1).